Gender differences in reactions to loan collection mechanisms: A large-scale natural field experiment - Bao, Leo; Huang, Difang (Journal of Financial Intermediation, 2026)
We study gender differences in on-time loan payment responsiveness to collection mechanisms using randomized dunning text messages sent to 17,545 FinTech borrowers. Reminder text messages significantly reduce delinquency rates relative to a no-message control, with messages incorporating social or financial incentives proving more effective. Women are more responsive to social pressure, while men are more sensitive to financial incentives. These results are robust to observable control variables and matching methods. Channel analyses indicate that gender differences in responsiveness to the existence and size of the incentive explain the observed gender differences under the social incentive treatment. However, only gender differences in sensitivity to the existence of incentives explain the gender difference in financial incentive treatments. These findings inform practitioners and policymakers that some seemingly gender-neutral practices may create unintended gender disparities in financial markets.